INDIGENOUS PROVERBS AS PEDAGOGICAL TOOLS FOR CONFLICT RESOLUTION: EDUCATIONAL USES OF XITSONGA PROVERBS IN SOUTH AFRICAN HOME LANGUAGE CLASSROOMS - Tinyiko Esther Chauke (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study examined how Xitsonga proverbs can cultivate conflict resolution skills in the South African Home Language classroom. It addressed rising interpersonal conflicts among learners and the limited use of indigenous oral traditions in classrooms. The study noted that emphasis on academic performance reduced opportunities for developing learners’ social and emotional competencies. Grounded in Indigenous Knowledge Systems and Culturally Relevant Pedagogy, the study emphasized integrating culturally familiar content to enhance engagement, moral development, and social cohesion. A qualitative design was employed, using classroom observations, semi-structured interviews, and learner artefact analysis. The study was conducted in selected Further Education and Training (FET) Phase secondary schools offering Xitsonga Home Language and involved Xitsonga Home Language teachers and learners. Purposive sampling was used to select participants with direct experience relevant to the study. Thematic analysis was used to interpret the findings. Learners improved in interpreting figurative meanings of proverbs and applying them to peer conflict resolution. Teachers observed enhanced empathy, restorative dialogue, collaborative problem-solving, moral reasoning, respect, and participation when proverbs were integrated into teaching. The study concluded that Xitsonga proverbs are effective pedagogical tools for promoting conflict resolution and affirming cultural identity. Findings highlight the importance of integrating indigenous knowledge into formal education to support both academic achievement and social development. This study contributes to discourse on culturally relevant pedagogy by demonstrating how indigenous oral traditions can foster conflict resolution and social cohesion in classrooms.